2018
DOI: 10.1071/hc17055
|View full text |Cite
|
Sign up to set email alerts
|

Skin lesions suspicious for melanoma: New Zealand excision margin guidelines in practice

Abstract: INTRODUCTION New Zealand guidelines for cutaneous melanoma management recommend excision biopsy specimens of suspected lesions have a 2 mm horizontal margin, and a deep margin into upper subcutis. AIM To assess guideline compliance of suspicious lesion biopsies taken in the community and in a hospital. METHODS Patients admitted to Waikato Hospital, Hamilton, for diagnostic or treatment melanoma surgery during the year ending February 2016 were retrospectively identified, and their demographic and biopsy ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…2 A biopsy is a fundamental and efficient way for skin lesion analyzing, which is painful, time-consuming, and some drugs might influence its results. 3 Dermoscopy is a skin imaging technique providing images with more clarity by magnifying the lesions (usually x3-x10). 4 Besides, computer-aided diagnosis (CAD) can be useful in melanoma detection using dermoscopy images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A biopsy is a fundamental and efficient way for skin lesion analyzing, which is painful, time-consuming, and some drugs might influence its results. 3 Dermoscopy is a skin imaging technique providing images with more clarity by magnifying the lesions (usually x3-x10). 4 Besides, computer-aided diagnosis (CAD) can be useful in melanoma detection using dermoscopy images.…”
Section: Introductionmentioning
confidence: 99%
“…However, its early detection helps the reduction of mortality rates 2 . A biopsy is a fundamental and efficient way for skin lesion analyzing, which is painful, time‐consuming, and some drugs might influence its results 3 . Dermoscopy is a skin imaging technique providing images with more clarity by magnifying the lesions (usually x3‐x10) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that there was no significant difference in melanoma-specific survival or overall survival between groups with 2-cm and 4-cm excision margins, for patients with localized CM thicker than 2 mm [11, 16, 17]. This research led to the present guidelines, including the National Comprehensive Cancer Network (NCCN), American Academy of Dermatology (AAD), and National Institute for Health and Care Excellence (NICE), which recommended the 2-cm margin for primary CM with a thickness of >2 mm [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Brian and Jameson include the hospital side of the melanoma story, concluding that New Zealand guidelines for melanoma excision biopsy need revision so that they provide more clinically meaningful measures that clinicians can use to audit their care. 13 Further relating to the practical use of guidelines, Reyneke, Jaye and Stokes examine the process of accepting and using care pathways in the Western Bay of Plenty. 14 We also have an array of papers about health care services.…”
Section: Reading Writing and Research Impactmentioning
confidence: 99%